Tailored Deterrence: Influencing North Korean Decision-Making - Raska, Michael (2016)
With strategic realities on the Korean Peninsula becoming more “fluid” or multi-faceted with multiple threat dimensions, defence planners in the US-ROK Alliance have been rethinking existing strategies for responding to different levels of threats posed by North Korea.